The Impact of Digitalization on the Constitutional Rights of Citizens - S. S. Vashurina (Теоретическая и прикладная юриспруденция)
The digitalization of public relations and state administration is the main trend of today. The introduction of digital technologies accompanies each of us in most areas of public life and affects personal, economic, political and cultural rights. The use of technology is intended to make it easier to exercise the rights for citizens; however, this trend creates conditions in which these rights can be violated. Within the framework of this study, the author considers the evolution of the concept of human and civil rights under the influence of the technological process and changes in tools that allow one to exercise one’s rights. The current legislation of the Russian Federation is primarily focused on the protection of personal data and personal security on the Internet, and by introducing special norms into basic laws, it creates conditions for the implementation of the rights such as active suffrage, the right to education, the right to access to justice and other rights. This approach is characterized by fragmentation, although digitalization forces the legislator and other regulators in this area to create a system of legal regulation.